Conditions Affecting the Performance of Peripheral Vein Cannulation during Hospital Placement: A Case Study - Monika Ravik; Anton Havnes; Ida Torunn Bjørk (Nursing Research and Practice)
Learning practical nursing skills is an important part of the baccalaureate in nursing. However, many newly qualified nurses lack practical skill proficiency required to ensure safe patient care. The invasive skill peripheral vein cannulation (PVC) is particularly challenging to learn and perform. This study explored conditions influencing nursing students’ learning and performance of the technical implementation of a PVC during their clinical placement period. A qualitative and descriptive case study design with two students in Norway practicing PVC during their clinical placement was conducted. One student who mastered the vein cannulation was compared with one student who did not. Data were collected in late 2012 using multiple data sources: semistructured interviews, ad hoc conversations, and video recordings. Video recordings of the two students’ cannula implementations were used to help clarify and validate the descriptions and to identify gaps between what students said and what they did. Thematic analysis of the transcribed text data enabled identifying themes that influenced skill performance. There were two overall themes: individual and contextual conditions influencing the technical implementation of a peripheral vein cannula. These findings were evaluated in terms of Benner’s work on scientific and practical knowledge, defined as “knowing that” and “knowing how.”